(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
The development of digital media, particularly YouTube, has created new opportunities for learning the Arabic language outside of formal education. However, the teaching strategies used on this platform have not been widely studied from a scientific perspective. This study examines how Arabic language teaching strategies are applied to the content presented on Sukardi Hasanudin’s YouTube account, from a pedagogical perspective. Based on this, the research aims to identify the teaching strategies and patterns in the presentation of learning content.The development of digital media, particularly YouTube, has created new opportunities for learning the Arabic language outside of formal education. However, the teaching strategies used on this platform have not been widely studied from a scientific perspective. This study examines how Arabic language teaching strategies are applied to the content presented on Sukardi Hasanudin’s YouTube account, from a pedagogical perspective. Based on this, the research aims to identify the teaching strategies and patterns in the presentation of learning content.